Characterization of management style based on a two-dimensional model in three types of dairy farms in the province of Lima, Peru - Ruiz-García, Luis (2023)
The aim of this research was to characterize the management style in three types of dairy farms in the province of Lima, Peru. A cross-sectional observational study was carried out in 18 dairy farms classified as family, informal and corporate farms. Surveys were applied to the managers and workers of each farm to evaluate the management style in two dimensions: "People" and "Tasks", based on the two-dimensional analysis model with six variables per dimension. Significant differences were found between management styles. In the "People" dimension, corporate farms had higher scores in the environment and relationships variables compared to informal farms (p<0.05), while family farms had a higher score in the relationship variable compared to informal farms (p<0.05). In the "Tasks" dimension, corporate farms had a higher score in the control, performance and objectives variables compared to the other two types of farms (p<0.05). Family farms exhibited a "social club" management style with a high focus on people and low on tasks (4.0 and 2.7, respectively), while the informal farms showed an "indifferent" style with low concern for both people and tasks (3.4 and 2.6 respectively). In contrast, corporate farms showed a “synergistic” style with a balance between people concerns and tasks (4.3 and 3.6 respectively). In conclusion, the research showed that the management style in the dairy farms of Lima varies depending on the type of livestock business. Corporate farms adopted a more synergistic and efficient style, while informal and family farms showed less structured styles and faced challenges in implementing management practices.